Nanotechnology manufacturing - Fonash, Stephen J.; Society of Manufacturing Engineers; Pen State University ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2003)
This video answers the big questions about nanotechnology like, what manufacturing advantages does Nanotechnology offers and how can Nanofabrication be done in a manufacturable way. This video also shows examples of what is currently being done
Code no : DV03PUB111
Title from title screen
Presenter: Stephen J. Fonash
Keywords: Nanotechnology; High technology; Manufacturing processes